A política faroleira no alvorecer da República no Pará: o Farol de Macapá (1889-1907) - William Gaia Farias; Gabriel Napoleão Veloso Neto (Navigator)
It’s the article’s goal to analyze the edification process of the lighthouses, in the context of the lighthousean policy that was established during the expansion of the maritime traffic, in the dawn of the brazilian repu-blic, especially during the period of the ‘Carta Marítima’ (1893-1907. We hope to verify the instalation of the towers in the coast, combined with the introduction of the modern objects and their reflection in the lighthousean policy in the Para state, debating about question that discuss the economical balance of the re-gion related to the Rubber Boom and to the flow of it’s production in the region. At last, we analyze the ins-talation of a lighthouse in the city of Macapá, which helps us to understand the necessity of such structure in the region as an object of guidance in the ‘Cabo Norte’ area.